Harmonics of CF and LED lamps - Maximum Penetration Perspective on Power Quality in Distribution Systems - Effah, Francis Boafo; Gasu, Philip; Okyere, Philip; Acakpovi, Amevi (Jurusan Teknik Elektro Universitas Andalas, 2020)
Global energy saving efforts have led to replacement of incandescent lamps with energy-efficient ones like light-emitting diode (LED) and compact fluorescent lamps (CFLs). These lamps, being non-linear loads, have the potential of injecting harmonics into distribution networks. In this paper, harmonics injection of common CFL and LED lamps at a facility point of common coupling is investigated. To gain insight into large scale penetration effects on power quality, field measurement results of popular lamps used in Ghana were replicated in MATLAB/Simulink through simulation. The field results showed that LED lamps exhibit more harmonics compared to CFL lamps. Maximum possible loading on a 100-kVA, 11kV/0.433kV distribution transformer was found to be 24.02% for CFL, 27.14% for LED, and 40.91% for a mixture of the two lamps, respectively, in order not to violate IEEE 519-2014 standard. The influence of other common loads such as ceiling fans on the lamps’ harmonics were assessed in the field measurement. The use of ceiling fans with the lamps in the facility reduced the harmonics and improved the power factor of the facility. Since the lamps exist in residential and commercial facilities with other loads, more penetration of energy-saving lamps in the distribution system will have little influence on power quality.Keywords: Compact fluorescent lamps, light emitting diodes, maximum power loading, total harmonic distortion, point of common coupling